The Proximity of the Wood(s) - Marder, Michael (Stasis, 2015)
When Artemy Magun invited me to participate in the conference celebrating the seventy-fifth anniversary of Vladimir Bibikhin’s birth, I did not have a shadow of a doubt. I knew that I had to discuss The Wood(s).1 Why this book in particular? After several years of work on the philosophy of vegetal life, this theme is incredibly close to me. But, besides such accidental proximity between Bibikhin’s seminar and my plant-thinking, there were also other reasons behind my decision. "The wood" or "the woods" is the first beginning, anticipating the Aristotelian conception of matter and, therefore, to a certain extent, the extra-philosophical source of philosophy. When all is said and done, we don’t and can’t talk about anything other than that, even if it seems to us that we are discussing something quite distant from the wood(s). Expressing this idea in Bibikhin’s language, let us say that we are captivated by the first beginning. We speak of nothing else but this beginning, even though the wood(s) is not at all a theme, but only the possibility of thematizing (everything). Narrowing it down to a theme, we lose that which we thematize, disrupt the "silence of the woods" (Bibikhin 2011: 52), and, by the same token, get lost, as though in a dark, impassable, lightless forest. Hence my first hypothesis: it makes no sense to talk about the wood(s) as such and it is only worth contemplating its/their proximity.